2015
DOI: 10.4238/2015.october.19.12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ESTs from black locust for gene discovery and marker development

Abstract: ABSTRACT. Black locust (Robinia pseudoacacia L.) is an ecologically and economically important species. However, it has relatively underdeveloped genomic resources, and this limits gene discovery and marker-assisted selective breeding. In the present study, we obtained large-scale transcriptome data using a next-generation sequencing platform to compensate for the lack of black locust genomic information. Increasing the amount of transcriptome data for black locust will provide a valuable resource for multi-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…In total, 991 miRNAs containing 671 novel miRNAs were obtained. Compared to the previous study of R. pseudoacacia, the sequencing results obtained in this study provide longer unigenes, and the overall results are better than before [45][46][47]. Overall 131,359 (74.69%) of the identified unigenes were successfully annotated using BLAST searches of the public Nr, Nt, Swiss-prot, GO, COG and KEGG databases, given the absence of genomic information on R. seudoacasia; 86 (26.88%) out of 320 known miRNAs were detected based on 82 other species' miRNAs from miRBase 21.0 (Supporting Table 9).…”
Section: Discussioncontrasting
confidence: 57%
“…In total, 991 miRNAs containing 671 novel miRNAs were obtained. Compared to the previous study of R. pseudoacacia, the sequencing results obtained in this study provide longer unigenes, and the overall results are better than before [45][46][47]. Overall 131,359 (74.69%) of the identified unigenes were successfully annotated using BLAST searches of the public Nr, Nt, Swiss-prot, GO, COG and KEGG databases, given the absence of genomic information on R. seudoacasia; 86 (26.88%) out of 320 known miRNAs were detected based on 82 other species' miRNAs from miRBase 21.0 (Supporting Table 9).…”
Section: Discussioncontrasting
confidence: 57%
“…However, studies have shown that dinucleotide repeats are the most predominant repeat motif type in many plants, especially in dicots such as Arabidopsis, peanut, soybean, bean and grape [38]. The result contrasts with both Wang et al (2015) [18] and Guo et al (2017) [19]. They identified that tri-nucleotide repeats were the most abundant repeat motif type in black locust.…”
Section: Frequency and Characteristics Of Ssrs In Black Locust Est Sementioning
confidence: 83%
“…For black locust, Lian et al (2002Lian et al ( , 2004 [15,16] and Mishima et al (2009) [17] have developed a total of 21 SSR markers. In addition, Wang et al (2015) [18] and Guo et al (2017) [19] have conduct a preliminary research on SSR loci in the EST sequences and a novel set of EST-SSR markers have been developed. However, compared with other species, the relatively limited number of efficient EST-SSR markers for black locust greatly obstructs its application to breeding research.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in novel gene discovery and molecular breeding in crop plants was under processing with the advent of high throughput technologies and the utilization of bioinformatics methodologies. 5,6 Transcriptome sequencing has, however caused a significant upshot in the expressed sequence tags (ESTs) collections in several plant species, including the non-model plant species. 7 The ESTs, which are generated by large-scale single pass sequencing of randomly picked cDNA clones, have been cost -effective and valuable resource for efficient and rapid identification of novel genes and development of molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…6,17 One can map ESTs to specific chromosome locations using physical mapping techniques, such as radiation hybrid mapping, happy mapping, or FISH. Alternatively, if the genome of the organism that originated the EST has been sequenced, one can align the EST sequence to that genome using a computer.…”
Section: Introductionmentioning
confidence: 99%